Current-controlled electroluminescence from light-emitting diodes based on Tm, Er, and Eu codoped Ga2O3 thin films. (1st August 2022) - Huang, Yafei; Deng, Gaofeng; Saito, Katsuhiko; Tanaka, Tooru; Guo, Qixin
Abstract: In this work, we report on the demonstration of an LED based on Tm, Er, and Eu codoped Ga2 O3 thin film. Current-controlled electroluminescence (EL) has been observed from the Ga2 O3 :(Tm+Er+Eu)-based LED with a relatively low driven voltage of ∼9 V. The EL spectra reveal that the observed light emission results from the combination of simultaneous blue, green, and red emissions from Tm 3+, Er 3+, and Eu 3+ ions, respectively. This strategy for LED shows great potential to achieve full color (white light) by intentionally changing the concentrations of Tm 3+, Er 3+, and Eu 3+ ions in Ga2 O3 without using any other phosphors.